Gestão das Políticas Governamentais Para os Recursos Hídricos, Recife, Pernambuco, Brasil - Renata Laranjeiras Gouveia (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2015)
The objective of this study was the examination of the Brazilian governmental policies at the national, state (Pernambuco) and municipal (Recife) levels focused on the conservation of water resources. The water, a natural resource, is a good inherent in the life of every human being and therefore needs to be preserved. The research used the means of documentary investigation and literature search, to the extent that examined the results of the international conferences and documents. The growing degradation of water resources generates on the international scene a concern so that they can be defined strategies to safeguard this precious as well. Concurrently with this, public policies are created at the national, state, and municipal spheres, and are discussed in the economic landscape and environmental for the setting of objectives and targets to which does not occur the collapse and that thus, this feature can be used in an appropriate manner so that in the future all citizens have access to a sufficient quantity and quality to meet your basic needs generating sustainability. The State of Pernambuco does not evade this need and creates alternatives to a management that bring benefits to the local population and conserve water resources. It is completing the survey that the formulation of public policies will not fully effective if there is no engagement of people, to raise awareness and make them about the problem of water resources.